Morbidity and Mortality Associated With Balloon Aortic Valvuloplasty: A National Perspective. (May 2017) - Alkhouli, Mohamad; Zack, Chad J.; Sarraf, Mohammad; Bashir, Riyaz; Nishimura, Rick A.; Eleid, Mackram F.; Nkomo, Vuyisile T.; Sandhu, Gurpreet S.; Gulati, Rajiv; Greason, Kevin L.; Holmes, David R.; Rihal, Charanjit S.
Abstract : Background—: The introduction of transcatheter aortic valve replacement (TAVR) led to renewed interest in balloon aortic valvuloplasty (BAV). We sought to assess contemporary trends in BAV utilization and their outcomes. Methods and Results—: The Nationwide Inpatient Sample was used to identify patients who underwent BAV between 2004 and 2013. In-hospital morbidity and mortality, and predictors of death after BAV were assessed. Outcomes of propensity-matched groups of patients undergoing elective BAV or TAVR were evaluated. BAV utilization increased from 707 cases in 2004 to 3715 cases in 2013 (national estimates). Procedural and in-hospital mortality were 1.4% and 8.5%, respectively. Vascular complications occurred in 7.0% of cases, blood transfusion in 17.5%, clinical stroke in 1.8%, and pacemaker implantation in 3.0%. The strongest predictors of in-hospital death were cardiogenic shock (odds ratio, 6.01; 95% confidence interval, 4.19–8.61; P <0.001), need for left ventricular assist device (odds ratio, 3.48; 95% confidence interval, 2.25–5.36; P <0.001), coagulopathy (odds ratio, 2.19; 95% confidence interval, 1.51–3.18; P <0.001), and low institutional volume of BAV (odds ratio, 1.58; 95% confidence interval, 1.06–2.37; P =0.03). In propensity-matched patients undergoing elective BAV or TAVR, rates of in-hospital mortality (2.9% versus 3.5%; P =0.60), clinical stroke (1.6% versus 3.1%; P =0.10), and vascular complications (8.2% versus 10.9%; P =0.14) were similar. However, BAV was associated with lower rates of pacemaker implantation (2.9% versus 8.0%; P <0.001) and blood transfusion (12.8% versus 22.9%; P <0.001). Conclusions—: In a contemporary national registry, BAV is associated with significant morbidity and mortality that are similar to TAVR. With the substantial increase in BAV utilization and the continuous improvement in TAVR outcomes, these data have important implications to aid clinicians in the selection of appropriate BAV candidates. Abstract : Supplemental Digital Content is available in the text.